Implementasi Pengelolaan Sarana dan Prasarana dalam Peningkatan Kualitas Pendidikan Berdasarkan Instrumen Akreditasi Satuan Pendidikan (IASP) Tahun 2020 di MTsN 1 Kota Bandung - Ramadhan, Fahri Sahrul; Nugraha, Mulyawan Safwandy (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2024)
Facilities and infrastructure are crucial components in enhancing the quality of education. This study aims to provide an overview of the implementation of facilities and infrastructure management, particularly in improving the quality of education. The data collection procedures were conducted through observation, interviews, and documentary studies with sources including the Head of Facilities and Infrastructure, the Head of Curriculum, teachers, students, and other stakeholders. Meanwhile, data analysis was carried out using a qualitative approach. The research findings indicate that the implementation of facilities and infrastructure management at MTs Negeri 1 Kota Bandung encompasses several discussions: (1) Planning of facilities and infrastructure, including needs analysis and projection of required facilities and infrastructure. (2) Organization of facilities and infrastructure, including inventorying and arrangement. (3) Implementation of facilities and infrastructure, including utilization and maintenance. (4) Monitoring of facilities and infrastructure, including performance monitoring and assessment. Based on the research results, it can be concluded that the implementation of facilities and infrastructure management in improving the quality of education, based on the Accreditation Instrument for Educational Units (IASP) for the year 2020 at MTs Negeri 1 Kota Bandung, achieved a level 4 with the highest performance achievement. Considering the accreditation results regarding facilities and infrastructure standards, MTs Negeri 1 Kota Bandung obtained a score of 94, indicating excellent management of facilities and infrastructure.